IMPLEMENTASI KEBIJAKAN JAMINAN KESEHATAN NASIONAL (JKN) PADA DINAS KESEHATAN KABUPATEN SIGI - Mariam, Mariam (Katalogis, 2016)
The National Health Insurance Scheme in Sigi indicate the existence of problems in the process of implementation. Among the problems is the lack of health personnel and facilities in direct health care unit, which resulted in the process of service to participants of the National Health Insurance does not seem optimal. By looking at the phenomena, the authors conducted this research is intended to analyze the implementation of the National Health Insurance Program policies in the county. The location of this research include Sigi District Health Office, Torabelo hospitals, and health centers Biromaru. The theory used is the theory of public policy implementation of Van Metter and Van Horn. The research method uses a qualitative approach, as well as the selection of techniques used informants propusive sampling technique. The informants is 7(seven) people. Techniques in data collection are observation, interviews and documents. The results showed that the implementation of the program the National Health Insurance at the District Health Office Sigi has not yet overall effective, due to the availability of several types of resources are needed to support the implementation of the program is not adequate, as the lack of human resources is still not ideal for workload and responsibility that must be completed, the capacity of health care facilities and infrastructure available no longer in accordance with the number of visits of participants to be served. The consequences of an impact on the service process are not optimal for the participants of the National Health Insurance.